2006
DOI: 10.1016/s0022-5347(05)00983-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Sexual Function of Holmium Laser Enucleation Versus Transurethral Resection of the Prostate: Results of a Prospective, 2-Center, Randomized Trial

Abstract: TURP and HoLEP significantly lowered the IIEF orgasmic function domain with no differences between techniques. This was caused by retrograde ejaculation. Marginal, nonsignificant erectile function improvement was reported after surgery in the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
124
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(145 citation statements)
references
References 19 publications
7
124
0
9
Order By: Relevance
“…Table 5 shows the most important English language papers of interest. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Use of validated questionnaires is essential in sexual function assessment. Soderdhal et al 16 showed that a nonvalidated questionnaire may cause false reports of ED.…”
Section: Discussionmentioning
confidence: 99%
“…Table 5 shows the most important English language papers of interest. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Use of validated questionnaires is essential in sexual function assessment. Soderdhal et al 16 showed that a nonvalidated questionnaire may cause false reports of ED.…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63] In a randomized comparison of TURP with holmium laser enucleating of the prostate, holmium laser enucleating of the prostate was not associated with worsening erectile function after surgery and there was no difference compared with TURP. 64 A number of studies related to Greenlight laser vaporization of the prostate describe no influence [65][66][67] or even improvement 68 of erectile function. In contrary to the previously mentioned studies, in another study in a group of preoperatively potent patients (IIEF-5418), a significant negative impact on erectile function following the Greenlight procedure was observed.…”
Section: Luts and Ed: Effects On Clinical Managementmentioning
confidence: 99%
“…There were no significant differences in late complication rates of ure-thral strictures, bladder neck contractures, or need for reoperation. In a comparison of the impact of each surgical technique on erectile function, both HoLEP and TURP equally lowered responses on the orgasmic domain of the International Index of Erectile Function questionnaire [25].…”
Section: Many Comparative Trials Of the Holep Technique Versusmentioning
confidence: 94%